Parents’ representations of primary school sports and academic achievement: socio-sportive approach - Zouaoui, Makrem (sports creativity, 2023)
This study deals with school sport and academic achievement through understanding the perspectives of parents of primary school students. It focuses on the factors that influence the correlation between school sport and academic achievement. The study discusses the variables of academic level and age of students’ parents and provides different theoretical and empirical results. The results of the study reveal that parents hold a negative perspective on school sport as they understand that it affects their kids’ academic performance negatively. Parents seem to argue that time limits, the absence of supervision and the lack of sport facilities are among the factors that can limit their kids’ academic ability. Parent also expressed the importance of sports for psychological and physical welfare of their kids.